2020
DOI: 10.48550/arxiv.2006.11729
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kiwifruit detection in challenging conditions

Mahla Nejati,
Nicky Penhall,
Henry Williams
et al.

Abstract: Accurate and reliable kiwifruit detection is one of the biggest challenges in developing a selective fruit harvesting robot. The vision system of an orchard robot faces difficulties such as dynamic lighting conditions and fruit occlusions. This paper presents a semantic segmentation approach with two novel image prepossessing techniques designed to detect kiwifruit under the harsh lighting conditions found in the canopy. The performance of the presented system is evaluated on a 3D real-world image set of kiwif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Figure 13(b) shows the pictures of kiwifruit in day and night conditions. 27 The moisture content present at the skin of the kiwifruit makes some changes in the night time captured images and needs additional focus.…”
Section: Role Of Night Time Imaging In Fruit Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 13(b) shows the pictures of kiwifruit in day and night conditions. 27 The moisture content present at the skin of the kiwifruit makes some changes in the night time captured images and needs additional focus.…”
Section: Role Of Night Time Imaging In Fruit Detectionmentioning
confidence: 99%
“…Processing of kiwifruit in overexposed condition has been depicted in. 27 For the detection a fruit in RGB colour space images has been converted in YCbCr colour space. From that it is observed that the blue colour space is more exposed to sunlight and hence replaced with green colour space.…”
Section: Detection Of Fruits In Overexposed Conditionsmentioning
confidence: 99%
See 1 more Smart Citation